Introduction: Eritrea’s Uneasy Futures and their Historical Contingencies - David O’Kane; Sabine Mohamed; Magnus Treiber (Modern Africa)
To introduce this special issue of Modern Africa, the editors review Eritrea’s current condition and consider its historical roots: they place this Horn of Africa state in a broader historical context, one where neither relevant comparative cases nor past precedents are limited to its region. Hopes that were once invested in Eritrea as a model developmental state have now, thirty years since its independence, been thoroughly disappointed. The human rights violations and persistent underdevelopment that make an Eritrean transition necessary are very real: equally real are the risks and dangers that would be involved in any such transition. Recent cases of failed transition are discussed here: so too are the possible routes Eritrea might take to a “developmental democracy.” This issue’s various contributions are then introduced and summarised.